A novel modified peptide derived from membrane‐proximal external region of human immunodeficiency virus type 1 envelope significantly enhances retrovirus infection. (19th November 2013) - Zhang, Lishuang; Jiang, Chunlai; Zhang, Huayan; Gong, Xin; Yang, Lan; Miao, Liang; Shi, Yuhua; Zhang, Yan; Kong, Wei; Zhang, Chuntao; Shan, Yaming
<x xml:space="preserve">Abstract</x> Efficient gene transfer is a critical goal in retroviral transduction. Several peptides capable of forming amyloid fibrils, such as the 39‐residue semen‐derived infection‐enhancing peptide (SEVI), have demonstrated the ability to boost retroviral gene delivery. Here, a 13‐residue peptide P13 (Ac‐671NWFDITNWLWYIK683) derived from the membrane‐proximal external region of the human immunodeficiency virus type 1 (HIV‐1) gp41 transmembrane protein, together with its 16‐residue peptide derivative (P16) were found to enhance HIV‐1 infection significantly. Both peptides, P13 and P16, could form amyloid fibril structures to potently enhance HIV‐1 infectivity. Further investigations showed that both aromatic Trp residues and cationic Lys residues contributed to the enhancement of HIV‐1 infection by these two active peptides. P16 could more effectively augment HIV‐1 YU‐2 infection than SEVI, implying its potential applications as a tool in the lab to improve gene transfer rates. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd.